Kiprah Doktor Yusuf Qardhawi Dalam Dakwah dan Gerakan Islam serta Pemikirannya tentang Etika Ekonomi - Djakfar, Muhammad (ULUL ALBAB Jurnal Studi Islam, 2005)
The name of Dr. Yusuf Qardhawi is not unfamiliar to the Islamic society as he is a visionary, cosmopolite, and ulema (Ismamic leader) whose thought on religion has been widley used as references.He is quite phenomenal, being a very productive ulema in the universe at the end of the twentieth century up to the beginning of this twenty first century. Therefore, it would be very interesting to conduct an in-depth study on what factors or cross-lines have influenced his productivity, what role he has in the dakwah and Islamic movement, as well as what his thought on economic ethic is. It can be concluded from this discourse that Qardhawi earned his great reputation not only from his individual intellectual capability, but also from an external factor. In this case, the presence of Ikhwanul Muslimin worked as the external factor which has brought him to fame.